Linear model for coputation of equilibrium point in bimatrix game - Vakrinienė , Sigutė; Sudžiūtė, Daina (Lietuvos matematikos rinkinys, 2021)
The methods for finding Nash equilibrium in bimatrix game are introduced in this paper.  Linear optimization model with binary variables for coputation of all equilibrium points in nongenerate bimatrix game is proposed.
Keywords: bimatrix game; equilibria; mixed-integer linear programming